MRI gadolinium dosing on basis of blood volume - Liu, Chia‐Ying; Lai, Shenghan; Lima, João A.C. (Magnetic resonance in medicine, 2019)
Purpose Gadolinium‐based contrast agents (GBCAs) for MRI are generally administrated in direct relationship to body weight. Instead, we propose a model for GBCA dosing on the basis of blood volume. The new method was tested by exploring the associations between MRI T1 mapping indices and weight in the MESA (Multi‐Ethnic Study of Atherosclerosis. Methods Empirically derived methods based on sex and body habitus were used to calculate blood volumes. GBCA dose (in mL) in blood (in L) was calculated as the injected volume divided by the blood volume (i.e., DBV). Of the 1219 participants with cardiac MRI T1 mapping, 845 studies had standard dose of 0.15 mmol/kg (cohort 1) and 166 studies had 30 mL of GBCA regardless of weight (cohort 2). We also created a specific cohort with similar DBV (N = 357; cohort 3). Results Postcontrast blood relaxation rate R1blood and DBV were significantly correlated (R = 0.641; P < 0.001). R1blood was significantly associated with weight in cohort 1 and 2, but the correlation coefficient was positive for cohort 1 and negative for cohort 2, indicating GBCA overdosing in cohort 1 and underdosing in cohort 2 in heavy relative to lean subjects. R1blood was not associated with weight in cohort 3. Simulated results demonstrated that less contrast should be administrated for heavy subjects compared to the conventional weight‐based dose. Conclusion GBCA dosing on the basis of blood volume could improve the efficacy and safety of contrast‐enhanced MRI studies. This method could be implemented to standardize dose and augment precision in study comparisons.